Evaluation of health state and growth of Gypsophila paniculata L. and Gypsophila repens L. groving in soil in variable fertilization - Maria Warner; Wojciech Antkowiak (Acta Agrobotanica, 2013)
The influence of NPK fertilization on plant growth and roots yield of Gypsophila paniculata and Gypsophila repens was investigated. The nutrients were applied in different proportions. The health state of Gypsophila was also analyzed. The pathogens isolated from plants showing the diseases symptoms represented eight species: Alternaria dianthicola Neergaard; Fusarium avenaceum (Fr.) Sacc.; Fusarium culmorum (W. G.Smith) Sacc.; F.equiseti (Cola) Sacc.; F.oxysporum Schlecht., Snyder et Hansen; F.sambucinum Fuck; Phytophthora sp. de Bary; Rhizoctonia solani K. Fusarium oxysporum and other species of fungi were isolated from Gypsophila paniculata, whilst from Gypsophila repens only Fusarium oxysporum was obtained.